Comparison of Clinical Characteristics Between Obese and Non-Obese Patients with Nonalcoholic Fatty Liver Disease (NAFLD) - Li Y (Dove Medical Press, 2021)
Yifang Li, Yanzhen Chen, Xing Tian, Shanshan Zhang, Jian Jiao Department of Gastroenterolgy & Hepatology, China-Japan Union Hospital, Jilin University, Changchun, 130033, People’s Republic of ChinaCorrespondence: Jian JiaoDepartment of Gastroenterology & Hepatology, China-Japan Union Hospital, Jilin University, Changchun, People’s Republic of ChinaTel +86 13756009567Fax +86 0431-84995850Email jjian@jlu.edu.cnObjective: Non-alcoholic fatty liver disease (NAFLD), previously thought to predominantly affect obese individuals, has also been shown to occur in subjects who have a relatively normal body mass index (BMI). Due to the normal BMI, non-obese NAFLD are easily to be ignored and eventually lead to potential liver injuries.Methods: A population-based cross-sectional study was conducted on 1608 cases with normal serum alanine aminotransferase (ALT) levels who were divided into an obese group (BMI ≥ 25 kg/m2) and a non-obese group (BMI < 25 kg/m2). NAFLD was diagnosed by ultrasound and Fibro Scan examination. Non-obese populations were divided into NAFLD group (CAP ≥ 240 db/m) and non-NAFLD group (CAP < 240 db/m). The incidence of NAFLD in the obese and non-obese populations and constituent ratios of genders, age, and serum levels of triglycerides (TG), cholesterol (CHOL), and blood glucose were compared. Risk factors of NAFLD in non-obese people were analyzed by multivariate logistics regression.Results: The occurrence of NAFLD was higher in the obese group than in the non-obese group, regardless of gender (P < 0.001). In the non-obese group, the occurrence of NAFLD in female patients was lower than that in male (P=0.001). The occurrence of NAFLD increased with age, with 50– 59 years being the peak age of incidence in both male and female. The peak age of NAFLD occurrence in non-obese male patients was more delayed than that in obese male patients. BMI (OR=1.311, P=0.000) and TG (OR=2.545, P=0.000) were risk factors for NAFLD in the non-obese population.Conclusion: Compared with obese population, the incidence of NAFLD in non-obese population was relatively low and more frequently in male than in female, the peak age of NAFLD occurrence in non-obese male patients was also delayed. BMI and TG should still be controlled to avoid the occurrence of NAFLD although the BMI of such patients is normal.Keywords: obese, non-obese, non-alcoholic liver disease, gender, characteristic